2008
DOI: 10.1529/biophysj.107.115253
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in the N-Terminal Region of Photoactive Yellow Protein: A Time-Resolved Diffusion Study

Abstract: The kinetics of conformational change in the N-terminal region of photoactive yellow protein (PYP) was studied by the time-resolved diffusion measurement. The transient grating signal that represented the protein diffusion of the ground state and pB state depended on the observation time range. An analysis of the signal based on the time-dependent diffusion coefficient clearly showed that protein diffusion changed with a time constant of 170 micros, corresponding to the pR(2) --> pB' transition. Since a previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 38 publications
8
40
0
Order By: Relevance
“…[25] In addition, the light induced changes of the radius of gyration of the M100L mutant of the full length PYP as observed by smallangle X-ray scattering are 5% [36] and are also small for truncated variants. [37] [38] Single molecule studies have additionally shown that the PAS domain is extended by several nm in the I 2 ′ state. [39] This is in line with the calculated radii of gyration of the P and (DEER and NMR derived) I 2 ′ structural ensembles which are 13.3 ± 0.08 Å and 15.4 ± 0.41 Å respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In addition, the light induced changes of the radius of gyration of the M100L mutant of the full length PYP as observed by smallangle X-ray scattering are 5% [36] and are also small for truncated variants. [37] [38] Single molecule studies have additionally shown that the PAS domain is extended by several nm in the I 2 ′ state. [39] This is in line with the calculated radii of gyration of the P and (DEER and NMR derived) I 2 ′ structural ensembles which are 13.3 ± 0.08 Å and 15.4 ± 0.41 Å respectively.…”
Section: Discussionmentioning
confidence: 99%
“…20,[31][32][33][34][35][36][37][38] Origins of D-change have been investigated and can be classified into two categories. The first category is related to photo-induced dimeriza- tion.…”
Section: Concentration Dependence Of the Diffusion Signalmentioning
confidence: 99%
“…The prediction that a salt bridge is correlated with the unfolding route can also be addressed experimentally. Recently, a time-resolved diffusion study suggested that the Nterminal region, including Asp20, loses α-helical content after the proton transfer (35). Varying the ionic strength of the environment of PYP has a profound effect on the formation of pB, as shown by time-resolved absorption and fluorescence spectroscopy (36).…”
mentioning
confidence: 99%